Development of a maintenance rounds format for information traceability and fault prediction at COTECMAR (2025)
This document presents the progress in designing a maintenance rounds system for COTECMAR, emphasizing its structure and software development. The system is tailored to meet several critical requirements: it features an intuitive design for crew members to ensure accurate readings of variables for each asset, provides administrator access for system and asset configuration, and complies with naval defense standards, particularly DEF STAN 00-60. Additionally, it integrates seamlessly with the Integrated Logistic Support (ILS) discipline. The project draws on knowledge from courses in Industrial Maintenance, Programming, and Data Structures, and so far, has involved acquiring skills in scientometrics for research. The developed prototype includes a user-friendly interface, a robust database management system, and a mobile application for accessibility. The testing phase involved implementing a maintenance round for the Common-Rail Series 2000 engine, which demonstrated the system’s functionality through accurate logging in the database. Key results from the testing phase indicated successful integration with the ILS model, ease of use, and robust data management, though areas for improvement such as system performance under load and data synchronization were identified. This project underscores the potential for significant advancements in maintenance management, offering a scalable and adaptable solution for COTECMAR’s future needs. By addressing the identified challenges and refining the system, it is poised to substantially enhance the operational efficiency and reliability of naval vessels.